A study of planning, design & improvement of surface drainage of Shah Alam / Mahmud Yusoff - Yusoff, Mahmud (1981)
Shah Alam is in the process of development. At this stage drainage forms one of the problems. Floods do occur in the law land arena and sedi mentation of siltation at certain main drains.